2012
DOI: 10.4137/bmi.s10092
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Circulating Inflammatory Biomarkers with Risk Factors for Colorectal Cancer in Colorectal Adenoma Patients

Abstract: Obesity and central adiposity are associated with colorectal cancer risk and have been linked to inflammation. Inflammation is a complex, interactive response that may most accurately be summarized through multiple, simultaneously measured cytokines. In this cross-sectional analysis, we investigated associations of circulating plasma levels of C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-1β (IL-1β), and a combined inflammation z score with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Concentrations of inflammation markers were comparable to those in the pilot trial, which had a much shorter gap between sample collection and laboratory measurement (21). Most importantly, associations of these biomarkers at baseline with sex, body measurements, and an oxidative balance score were consistent with previous findings from our group (42,45,46) and other groups (e.g., refs. [47][48][49], supporting the validity of our biomarker measurements.…”
Section: Discussionsupporting
confidence: 87%
“…Concentrations of inflammation markers were comparable to those in the pilot trial, which had a much shorter gap between sample collection and laboratory measurement (21). Most importantly, associations of these biomarkers at baseline with sex, body measurements, and an oxidative balance score were consistent with previous findings from our group (42,45,46) and other groups (e.g., refs. [47][48][49], supporting the validity of our biomarker measurements.…”
Section: Discussionsupporting
confidence: 87%
“…The choice of a composite inflammatory score is somewhat arbitrary, and there are multiple methods of computing a composite inflammatory score [48]. The method that we presented in this paper of examining those with two or more inflammatory markers in the top quartile has also been published previously and represents a more specific indicator of systemic inflammation than a high level of just one inflammatory marker [4, 4951].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of colorectal polyps focused on select markers of inflammation, most commonly IL-6, TNF-α and c-reactive protein (CRP) (Hopkins et al, 2012; Il'yasova et al, 2005; Kim et al, 2008; Wild et al, 2010). These studies found IL-6, TNF-α, and CRP as well as non-cytokine markers, such as carcinoembryonic antigen and ferritin, are positively associated with the presence of colorectal adenomas as well as with general cancer incidence.…”
Section: Discussionmentioning
confidence: 99%